Climate change impacts and adaptation strategies in tourism sector in Africa: a systematic literature review - Lucas Massay; Abiud Kaswamila; Kalista Higini Peter (African Business Management Journal, 2025)
Tourism sector is of great importance to the economies of many African countries. However, it faces significant challenges due to climate change impacts. This review paper evaluates various climate change impacts on African tourism and examines adaptation strategies implemented across the continent. 49 relevant papers were identified through a systematic review. An increase in extreme weather conditions, altered precipitation patterns and rising temperatures threaten the viability of key tourist attractions. These results highlight key issues such as the loss of biodiversity, the disruption of wildlife migrations, beach erosion and infrastructure damage. As a result, different adaptation strategies have been implemented. Resilient infrastructure development, diversification of tourism products, and community engagement and education programs are some examples. A variety of technologies, such as early warning systems and flexible itinerary options, are also mentioned in reviews. Concrete policy gaps such as limited access to climate finance for tourism specific adaptation in vulnerable destinations are also discussed. The paper concludes by discussing the implications of these findings for policy makers, the private sector and local communities. Finally, the paper discusses limitations of the study including reliance on English peer-reviewed literature and the omission of grey literature. The paper also suggests areas for further research including expanding coverage to underrepresented regions, using mixed methods approaches to assess sustainability and to include nature-based solutions.